Lifelong Learning in Social Work Career - Mira Ćuk; Ana Gavrilović; Draško Gajić; Ljubo Lepir (Društvene i Humanističke Studije, 2017)
Professional development and permanent professional training became a need and necessity for social workers to perform their work. Everyday social and economic changes lead to complexity andmultiplication of problems for individuals, social groups and communities requesting from social work appropriate responses in fulfilment of its varying purposes. Education of social workers does not end at the first cycle of academic studies; it should be a continuous process that includes permanent (lifelong) learning and, often specialist development. Such “policy of profession” is not inherent solely to social work but it is a generally proclaimed vocational need in the current moment of civilisation. In the recent decades, the European Union and many European countries developed within their policies of growth and education a concept of lifelong learning. The overall goal of lifelong learning is provision of necessary quantum of theoretical and practical knowledge within the professional field; that is the change of profession and acquisition of higher level of knowledge or innovation of knowledge and increase of competences and capabilities for efficient and effective performance in accordance with requirements of modern standards of quality.Social workers in the Republic of Srpska have a legal and professional obligation to develop professionally to perform their job. While accomplishing this obligation, they do not have a systematic and organized support provided within their social systems or within their organizations. In the absence of research and development institutions in the field of social protection and social work as well as of accredited programs for education, an active role in the lifelong learning process of social workers in the Republic of Srpska should be realized through study programs for high education of social workers and through programs that have the necessary resources for this purpose.